Effect of botulinum toxin injection on pain severity and quality of life among patients with postherpetic neuralgia - R Prasuna; Ajay Reddy Aeerabolli (Wolters Kluwer Medknow Publications, 2023)
Background: Herpes zoster and postherpetic neuralgia (PHN) results from reactivation of varicella-zoster virus. Pain increases sharply with advancing age and the elderly are more inclined to suffer. If herpes zoster is not treated early, patients may develop PHN. For some, it can persist for 1-2 years. Botulinum toxin injection (BTX-A) has been useful for patients suffering from PHN pain. Objective: The objective of this study was to study the effect of botulinum toxin on pain severity and quality of life in patients with PHN. Methods: A hospital record-based follow-up study was carried out among 30 PHN patients treated with hypodermic injection of BTX-A. Before injection, we measured Visual Analog Score (VAS) for pain severity and the Quality of Life (QOL) Scale using short form survey-36 (SF-36) score. BTX-A injections were given, and patients were followed every month for 6 months. During follow-up, VAS, QOL, pain frequency, and analgesic use were measured. Results: Majority were 60-69 years (40%). The proportion of males and females was not much different. Mean pain severity reduced significantly from 8.9 to 5.8 at 6 months. QOL improved significantly in 6 months. Pain frequency decreased significantly from 22.33 to 18.56 at 6 months. Mean analgesics use was 87.43 which reduced significantly to 7 at 2 weeks after BTX-A and then slowly increased to 7.66 at 4 weeks, to 8.23 at 12 weeks, and 10.4 at 24 weeks. Conclusion: Using BTX-A for treating PNH is promising and gives long-lasting results. It can be considered a valid approach in the treatment of PNH, especially in nonresponsive patients.